The Nakuru Posterior Segment Eye Disease Study: Methods and Prevalence of Blindness and Visual Impairment in Nakuru, Kenya - MATHENGE, Wanjiku; BASTAWROUS, Andrew; FOSTER, Allen; KUPER, Hannah (Ophthalmology (Rochester, Minn.), 2012)
To estimate the prevalence of blindness and visual impairment (VI) in adults aged ≥50 years in the Nakuru district of Kenya and to identify sociodemographic risk factors for these conditions. We also sought to validate the Rapid Assessment of Avoidable Blindness (RAAB) methodology. There were 5010 subjects enumerated for this study. Of these, 4414 participants underwent examination, for a response rate of 88.1%. Cross-sectional, population-based survey. Cluster random samplings with probability proportionate to size procedures were used to select a representative cross-sectional sample of adults aged ≥50 years. Each participant was interviewed, had distance visual acuity (VA) measured with reduced logarithm of the minimal angle of resolution tumbling-E chart, underwent autorefraction, and thereby had measurements of presenting, uncorrected, and best-corrected VA. All participants, regardless of vision, underwent detailed ophthalmic examinations including slit-lamp assessment and dilated retinal photographs. Visual acuity of <6/12. A representative sample of 4414 adults were enumerated (response rate, 88.1%). The prevalence of blindness (VA < 3/60 in better eye) was 1.6% (95% confidence interval [CI], 1.2-2.1%) and of VI, 0.4% (95% CI, 0.3-0.7%); 8.1% (95% CI, 7.2-9.2%); and 5.1% (95% CI, 4.3-6.1%) were severely (<6/60-3/60), moderately (<6/18-6/60), or mildly (<6/12-6/18) visually impaired, respectively. Being male, having less education, having Kalenjin tribal origin, and being ≥80 years old were associated with increased blindness prevalence. Prevalence estimates were comparable to a RAAB performed in the same area 2 years earlier. This survey provides reliable estimates of blindness and VI prevalence in Nakuru. Older age and tribal origin were identified as predictors of these conditions. This survey validates the use of RAAB as a method of estimating blindness and VI prevalence.